Thelaziosis caused by Thelazia callipaeda Railliet et Henry, 1910 (literature review) - L. A. Glazunova; Yu. V. Glazunov (Российский паразитологический журнал)
The purpose of the research is to analyze literature data on epizootology, morphology and biology of Thelazia callipaeda, and on clinical signs of thelaziosis.Thelaziosis caused by Th. callipaeda is widespread and not limited to Southeast Asian countries. At the end of the last century, autochtonous infection cases of thelaziosis were noted in Italy, and later the disease was recorded in France, Switzerland, Germany, Spain, Belgium, Portugal, Romania, Bosnia, Herzegovina, Croatia, Greece, Slovakia, Serbia, Turkey, Hungary, Moldova, Austria, Czech Republic, Poland, etc. Cases of thelaziosis recorded in the United States of America and the Russian Federation were most likely allochthonous and imported from contaminated areas. In Russia, canine thelaziosis was recorded in Moscow, St. Petersburg and Tyumen. It was found that definitive hosts of Th. callipaeda were not only cats, dogs or humans, but also many species of wild animals, namely, gray wolf, red fox, pine marten, hare, wild cat, Iberian wolf, European grey rabbit, beech marten, pine marten, golden jackal, European badger and brown bear. The prevalence of Thelazia infection among populations of wild animals reached 38.1%. The maximum number of helminths found in one animal was 96 specimens. In the life cycle of Th. callipaeda, males of the fruit fly Phortica variegata and Ph. okadai, which can keep Thelazia larvae in their bodies for up to 180 days are involved. Phylogenetic analysis of the cox1 gene showed that Th. callipaeda isolated from diseased animals in different countries belonged to haplotype-1, which was common in Europe.